Coloniality in Farming: Disempowerment in the Margins and the Path to Decoloniality - Laniog, Jehu (Archīum Ateneo, 2024)
Coloniality, as defined by Walter Mignolo, is the complex matrix of power dominated by Western hegemony that holds places beyond the West within its grip. The state of coloniality, established through decades of colonial rule, introduced Western forms of political and economic systems exogenous to colonized spaces, heavily influencing the current trajectory of development in various nations across the globe. This presentation gazes into the role of the state in disempowering the margins through agricultural policies and how this magnifies coloniality in farming communities. In an archipelago, the call for decoloniality is an action towards multifaceted empowerment through a pluriversal future.